Commodity, Immunity, and Struggle: (Re)visiting Senses of Community in ELT - Posada Ortiz, Julia Zoraida; Castañeda Peña, Harold (Colombian Applied Linguistics Journal, 2021)
This article comprises part of a broader doctoral research project that seeks to explore the senses of community of four English language pre-service teachers (ELPTs) of a public university in Bogotá, Colombia. This study used a relational methodology that introduces an interepistemic dialogue between mainstream research and the Indigenous Research Paradigm. The data collection process was carried out through five sessions jointly agreed upon and designed with the participants. The main data collection instruments were autobiographies, which were a joint construction, and transcripts of the sessions. The research results show that the university, the English language teacher education program (ELTEP) and the practicum, among others, are part of a constellation of communities of fear or communities that represent a challenge. It was concluded that it is possible to understand the constellation of fear through an alternative theoretical framework that includes community as commodity, as immunity, and as struggle. This study contributes to research trends that seek to privilege the research participants’ voices and offers a different way to approach communities in ELT.